Genetic variation and cryptic lineage diversity of the Nigerian red-headed rock agama Agama agama associate with eco-geographic zones. Issue 6 (8th March 2019) - Nneji, Lotanna M; Adeola, Adeniyi C; Yan, Fang; Okeyoyin, Agboola O; Oladipo, Ojo C; Saidu, Yohanna; Samuel, Dinatu; Nneji, Ifeanyi C; Adeyi, Akindele O; Onadeko, Abiodun B; Olagunju, Temidayo E; Omotoso, Olatunde; et al.
Abstract: Nigeria is an Afrotropical region with considerable ecological heterogeneity and levels of biotic endemism. Among its vertebrate fauna, reptiles have broad distributions, thus, they constitute a compelling system for assessing the impact of ecological variation and geographic isolation on species diversification. The red-headed rock agama, Agama agama, lives in a wide range of habitats and, thus, it may show genetic structuring and diversification. Herein, we tested the hypothesis that ecology affects its genetic structure and population divergence . Bayesian inference phylogenetic analysis of a mitochondrial DNA (mtDNA) gene recovered four well-supported matrilines with strong evidence of genetic structuring consistent with eco-geographic regions. Genetic differences among populations based on the mtDNA also correlated with geographic distance. The ecological niche model for the matrilines had a good fit and robust performance. Population divergence along the environmental axes was associated with climatic conditions, and temperature ranked highest among all environmental variables for forest specialists, while precipitation ranked highest for the forest/derived savanna, and savanna specialists. Our results cannot reject the hypothesis that niche conservatism promotes geographic isolation of the western populations of Nigerian A. agama . Thus, ecological gradients and geographic isolation impact the genetic structure and population divergence of the lizards . This species might be facing threats due to recent habitat fragmentation, especially in western Nigeria. Conservation actions appear necessary.